Ceramic restoration repair: report of two cases - Luís Henrique Araújo Raposo; Natália Antunes Neiva; Gisele Rodrigues da Silva; Hugo Lemes Carlo; Adérito Soares da Mota; Célio Jesus do Prado; Carlos José Soares (University of São Paulo, 2009)
The esthetic and functional rehabilitation of patients with multiple missing teeth can be performed with several techniques and materials. Ceramic restorations provide reliable masticatory function and good esthetics. However, fracture can occur in some cases due to their brittle behavior. In some cases, the replacement of an extensive prosthesis is a problem due to the high treatment cost. In this paper, two cases are presented, in which fractures occurred in extensive metal-ceramic fixed partial dentures, and their replacement was not possible. Ceramic repair was chosen and the sequences of treatment with and without presence of the ceramic fragment are also discussed. The cases illustrate that, in some situations, fractured metal-ceramic partial dentures can be successfully repaired when prosthetic replacement is not a choice. Prosthodontists must use alternatives that allow a reliable repair to extensive metal-ceramic fixed partial dentures. Surface preparation of the ceramic with hydrofluoric acid in conjunction with a silane coupling agent is essential for a predictable bonding of composite resin. The repair performed with composite resin is an esthetic and functional alternative when extensive fixed partial dentures cannot be replaced.